Thrown in at the deep end? Perceptions of burdens, gains, and contributions to the integration of refugee students among teachers with(out) target group-specific professional knowledge - Spanner, Franziska; Maué, Elisabeth (Frontiers in Sociology, 2022)
In Germany, young migrants and refugees whose German language skills are not sufficient for attending regular classes are assigned to so-called preparation classes. The main objective of these classes is to teach German language skills and thereby prepare students for regular classes or vocational education and training. Teachers in these classes face special challenges which are beyond the requirements for teaching regular classes: They have to teach a group of students that is highly heterogeneous in several key respects, they have to deal with a dearth of institutional support and guidance, and they have a major responsibility regarding their students’ integration into the host country. Therefore, this paper asks, first, what target group-specific professional knowledge teachers possess and, second, to what extent this knowledge reduces the teachers’ stress and raises their perception of teaching successfully. Our survey of 48 teachers of refugees in prevocational preparation classes in the German Federal State of Baden-Württemberg shows that the majority of teachers achieved useful knowledge for teaching refugees, e.g. dealing with trauma and post-traumatic stress disorder, acquiring the German language, or language-sensitive teaching, by attending professional training. Furthermore, most of the teachers saw immigration to Germany as both a problem and an opportunity. Despite generally low stress levels the teachers were extremely stressed by the heterogeneity in their students’ performance, especially those teachers who had completed professional training. Students’ cultural heterogeneity was not perceived as stressful either by teachers with or teachers without professional training. The teachers felt they had the most success in helping their students learn German and managing everyday life. In general, the success in teaching perceived by the teachers was mixed. Additional qualitative analyses of answers to open questions show that teachers teach their students not only in school subjects but also more generally in everyday skills for living in Germany. Further, teachers appreciate the students’ willingness to learn and gratitude and perceive themselves as supporters of their integration while they criticize their working conditions. The findings are discussed against the institutional and contextual background of young refugees’ education in Germany and the special role of teachers in it.